Pelatihan Digital Marketing dengan Aplikasi Tiktok Shop untuk Anggota Koperasi UMKM Tajur Halang Makmur - Haryanto, Dicky; Alawiah, Enok Tuti; Yunandar, Rahmat Tri; Apriyani, Helina (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Community Service is one of the routine activities in implementing the Tridharma of Higher Education as a form of moral responsibility to the surrounding community. The activities carried out by the Bogor City Campus Information Systems Study Program this semester are in collaboration with Tajur Halang Makmur Micro, Small and Medium Enterprises which is located at Ruko Ning's Residence Jalan Raya Kalisuren, Kalisuren Village, Tajurhalang District, Bogor Regency. This training aims to improve the quality and role of cooperatives and MSMEs in spurring economic growth for members and society. Currently Tajur Halang Makmur UMKM has members consisting of members of the Tajurhalang Makmur sub-district MSME forum and all Indonesian citizens residing in Bogor Regency, who are also users of production material services, production goods services and/or users of production goods. The problem currently faced by partners is promotion and marketing, where currently marketing is still limited to members only, so this makes sales difficult. As a result of this training activity, partners' knowledge and skills increased in online product marketing through the TikTok application and digital marketing skills to market MSME products more widely